Blow-Up Rate Estimates for a System of Reaction-Diffusion Equations with Gradient Terms - Maan A. Rasheed; Hassan Abd Salman Al-Dujaly; Talat Jassim Aldhlki (International Journal of Mathematics and Mathematical Sciences)
This paper is concerned with the blow-up properties of Cauchy and Dirichlet problems of a coupled system of Reaction-Diffusion equations with gradient terms. The main goal is to study the influence of the gradient terms on the blow-up profile. Namely, under some conditions on this system, we consider the upper blow-up rate estimates for its blow-up solutions and for the gradients.